Relationships between objective acoustical measurements and architectural features in churches - António Pedro O. Carvalho (1994)
This study reports on acoustical field measurements in a major survey of Roman Catholic churches in Portugal that were built in the last 14 centuries. Series of monaural acoustical measurements were taken at several source and receiver locations in each church. The measurements included Reverberation Time, Early Decay Time, Early to Late Sound Index, Early to Total Energy Ration, Center Time, Loudness and two Bass Ratios. This paper concentrates on the relationships of these 8 Room Acoustic Parameters with 13 Architectural Features of the churches.